2019
DOI: 10.1177/1120700018825430
|View full text |Cite
|
Sign up to set email alerts
|

The clinical presentation, diagnosis and pathogenesis of symptomatic sports-related femoroacetabular impingement (SRFAI) in a consecutive series of 1021 athletic hips

Abstract: Aim: To examine the pathogenesis and clinical presentation of sports-related femoroacetabular impingement (SRFAI) in a large consecutive series of symptomatic athletes. Methods: Between January 2009 and February 2017 prospectively collected data from competitive athletes within the Gaelic Athletic Association (GAA), and who subsequently underwent arthroscopic treatment for symptomatic FAI, were analysed. Data was collected using internationally validated health questionnaires (Harris Hip Score, UCLA, SF-36, WO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 49 publications
3
28
0
7
Order By: Relevance
“…The mean alpha angle was 60.9° in our study, and it was similar to that found in other studies: 62.8° for high-level athletes 1 ; 60° for high-level athletes and 59° for recreational athletes 24 ; and 61° for professional athletes. 26 The mean alpha angles among sports categories were also similar to the data reported by Nawabi et al. 1 for high-level athletes: for endurance sports, 60° in our study compared to 55.8°; for rotational running sports, 62° in our study compared to 61.4°; for flexibility sports, 58° in our study compared to 57.9°; and for asymmetric overhead sports, 62° in our study compared to 63.5°.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean alpha angle was 60.9° in our study, and it was similar to that found in other studies: 62.8° for high-level athletes 1 ; 60° for high-level athletes and 59° for recreational athletes 24 ; and 61° for professional athletes. 26 The mean alpha angles among sports categories were also similar to the data reported by Nawabi et al. 1 for high-level athletes: for endurance sports, 60° in our study compared to 55.8°; for rotational running sports, 62° in our study compared to 61.4°; for flexibility sports, 58° in our study compared to 57.9°; and for asymmetric overhead sports, 62° in our study compared to 63.5°.…”
Section: Discussionsupporting
confidence: 91%
“… 24 , 25 Carton et al. 26 reported higher prevalence of male gender, 93%, in their study. These demographic differences among studies may be related to the sports and exercise culture in each country.…”
Section: Discussionmentioning
confidence: 70%
“…It has also been associated with the development of early hip osteoarthritis. 11,19,41 The concept of hip impingement was appreciated by Dr Smith-Petersen 44 in 1936, but FAI was first described by Myers et al 34 in 1999. Ganz et al 18 defined FAI as a condition that may arise from abnormal morphology involving the proximal femur and/or the acetabulum, or it may occur in patients who subject the hip to excessive and supraphysiological ranges of motion.…”
mentioning
confidence: 99%
“…Femoroacetabular impingement (FAI) syndrome (FAIS) 11 is a common diagnosis in high-level athletes who present with hip pain. 3,13,19,27 Numerous sports, including popular collegiate activities (soccer, football, ice hockey, etc), have been associated with increased risk for the development of FAIS. 6,22,25 Nawabi et al 19 categorized the different sports into 6 groups (cutting, contact, impingement, endurance, asymmetric/overhead, and flexibility sports) based on the biomechanical demand on the hip, to better understand the development and clinical course of FAIS in athletes.…”
mentioning
confidence: 99%